Sistem Rantai Pasok Produk Obat-Obatan - Aditya Rianda; Sri Eka Oktafani; Ikhsan Akmal; Zulfa Khairani; M. Gilang DP (Jurnal Optimasi Sistem Industri, 2011)
PT. Bayer Indonesia is a global enterprise with core competencies in health, nutrition and high-tech materials. As the core company operations, PT. Bayer Indonesia produces and markets various drugs and over-the-counter, as well as products for the agricultural industry. One of the products produced by this company are Aspirin and Calcium D Redoxon (CDR) Fortos. Material and information flows along the value-added chain becomes more dynamic. Supply Chain Management (SCM) is a method, tool, or approach to management. Demand management of PT. Bayer Indonesia is to capture information related to forecasting (forecasting), order entry, orderpromising, branch warehouse requirements. Forecasting methods used by these companies is a method of MRP (Material Requirement Planning). Supplier selection mechanism is performed by PT Bayer Indonesia is by selecting suppliers, supplier evaluation, supplier optimization, and material ordering and payment.